Permeable laminated grid ecological bank protection material suitable for improvement of dredged soil green material and preparation method of permeable laminated grid ecological bank protection material
By using composite modified agents and permeable laminated mesh structure design, the problems of poor environmental compatibility, mechanical properties defects and shrinkage cracking in dredging soil improvement technology are solved, and high-strength, permeability and ecologically friendly shore protection materials are achieved, which are suitable for ecological restoration of coasts and lakes.
Patent Information
- Application Number
- CN202510528476.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-25
- Publication Date
- 2025-08-26
AI Technical Summary
The existing dredging soil improvement technology has problems such as poor environmental compatibility, mechanical performance defects and severe shrinkage and cracking, and it is difficult to meet the wave impact resistance of air-transmitted structures.
A composite improver consisting of steel slag micro powder, red mud activator, diatomaceous earth, biochar, calcium lignin sulfonate, nano-alumina, calcium sulfate whiskers and activated magnesium oxide is used to combine with the design of the air-permeable laminated mesh structure to form a green improved material for dredged soil. Through gelling reaction, C-(N)-A-S-H gel and ettringite, magnesite and other substances are generated to improve the mechanical properties and ecological compatibility of the material.
It significantly improves the compressive strength and permeability of dredged soil, reduces the drying shrinkage rate, enhances wave energy dissipation efficiency and vegetation coverage, and is suitable for coastal and river and lake shoreline restoration projects with frequent tidal effects.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of intersection of construction engineering materials and ecological restoration, and in particular relates to a permeable laminated grid ecological bank protection material suitable for improving dredged soil green materials and a preparation method thereof. Background Art
[0002] Current dredged soil improvement technology has three major pain points: poor environmental compatibility: the pH value of cement-based materials is greater than 12.0, leading to alkalinization of the waters around the revetment (cited from the Journal of Environmental Management, 2020); mechanical performance defects: the 28-day compressive strength of traditional solidified soil is ≤10MPa, and the permeability coefficient is less than 0.5×10 -3 cm / s, which makes it difficult to meet the wave impact resistance requirements of the permeable structure (cited from Coastal Engineering, 2021); shrinkage cracking is serious: the drying shrinkage rate of conventional improved materials is greater than 0.1%, and the crack incidence rate of the revetment structure is ≥60% after 3 years of service. Summary of the Invention
[0003] In view of this, the present invention aims to propose a permeable laminated grid ecological revetment material suitable for improving dredged soil green materials and a preparation method thereof, so as to solve at least one technical problem in the background technology.
[0004] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0005] A green improver for dredged soil, comprising the following components by mass percentage:
[0006] 20-30 parts of steel slag powder;
[0007] 15-25 parts of red mud activator;
[0008] 10-15 parts of diatomaceous earth;
[0009] 8-12 parts of biochar;
[0010] 5-8 parts of calcium lignin sulfonate;
[0011] 3-5 parts of anionic polyacrylamide;
[0012] 2-4 parts of nano-alumina;
[0013] 1-3 parts calcium sulfate whiskers;
[0014] 3-6 parts of calcium sulfoaluminate expansion agent;
[0015] 2-4 parts of activated magnesium oxide;
[0016] 1-3 parts of sodium silicate powder.
[0017] Furthermore, the D50 of the steel slag powder is ≤ 50 μm;
[0018] The red mud activator is pretreated with potassium dihydrogen phosphate and calcined at 600℃, with a specific surface area of ≥150m 2 / g;
[0019] Diatomaceous earth is a modified nanoporous structure with a pore size of 10-50nm;
[0020] Biochar is the product of pyrolysis of agricultural and forestry waste at 500°C in the absence of oxygen;
[0021] The purity of calcium lignin sulfonate is ≥90%;
[0022] The molecular weight of anionic polyacrylamide is 8-12 million;
[0023] Nano-alumina is γ phase and the particle size is ≤100nm;
[0024] The aspect ratio of calcium sulfate whiskers is 20:1-30:1;
[0025] Calcium sulphoaluminate expansion agent is CSA (calcium sulphoaluminate) and Ca4Al6SO 16 (tetracalcium hexaaluminum sulfate);
[0026] The specific surface area of active magnesium oxide is ≥200m 2 / g, and the active magnesium oxide is coated with citric acid;
[0027] The modulus of sodium silicate powder is 2.8-3.0.
[0028] Furthermore, the molar ratio of the calcium sulfoaluminate expansion agent to the calcium sulfate whiskers is 1:1.2-1.5;
[0029] And / or, the carbonization reaction rate of the activated magnesium oxide matches the dredged soil solidification process within a degree of ±15%.
[0030] A method for preparing a porous laminated grid ecological revetment material suitable for improving dredged soil green materials comprises the following steps:
[0031] S1: Mix the above-mentioned dredged soil green improver with the dredged soil dry material and stir to form a homogeneous slurry;
[0032] S2: injecting the homogenized slurry into the mold and pressing it into a hollow laminated grid unit through a hydraulic molding machine;
[0033] S3: Carry out natural maintenance on the permeable laminated grid units to form a permeable laminated grid ecological bank protection material suitable for the improvement of dredged soil green materials.
[0034] Furthermore, in step S1, the dredged soil green improver is added at 8-15% of the dry mass of the dredged soil;
[0035] The stirring to form a homogeneous slurry includes using a double-shaft forced mixer to stir at a speed of 60-80 r / min for 5-8 minutes to form a homogeneous slurry.
[0036] Furthermore, in step S2, the hydraulic molding machine molds the hollow laminated grid units at a pressure of 15-25 MPa.
[0037] Furthermore, the open laminated grid structure in step S2 includes a plurality of single-layer mesh surfaces arranged in sequence, the single-layer mesh surfaces are stacked in a stepped manner, and ribs are provided between the single-layer mesh surfaces;
[0038] An inverted cone-shaped protrusion is provided above the single-layer mesh surface, and a groove corresponding to the inverted cone-shaped protrusion is provided below the single-layer mesh surface. Mechanical interlocking is achieved between several single-layer mesh surfaces through the inverted cone-shaped protrusions.
[0039] Furthermore, the single-layer mesh surface is distributed in an array of orthogonal diamond holes, and the aperture of the orthogonal diamond holes of the single-layer mesh surface is 80-120 mm;
[0040] The rib width is 50-80mm; the offset distance of the open laminated grid structure is 1 / 3-1 / 2 of the aperture.
[0041] The height of the inverted cone-shaped protrusion is 5-8 mm, and the inclination angle is 45°-60°;
[0042] The side of the rib plate is provided with a V-shaped root guide groove with a width of 3-5mm, and vertical seepage channels with a diameter of 10-15mm are vertically provided between the layers of the single-layer mesh surface.
[0043] The above-mentioned method for preparing the permeable laminated grid ecological revetment material improved with dredged soil green materials has a compressive strength of 5-25 MPa.
[0044] The wave force attenuation coefficient η of the permeable laminated grid ecological revetment material improved with dredged soil green material meets the following requirements: η=1-HtHi≥0.65, and the test conditions are wave period T=5s and wave height H=2m;
[0045] Where Ht is the transmission wave height, in meters;
[0046] Hi is the incident wave height, in meters.
[0047] This application is applicable to coastal and river and lake shoreline restoration projects with frequent tidal action and high ecological sensitivity.
[0048] The main gelling phase is C-(N)-ASH gel formed by steel slag powder (CaO·SiO2·Al2O3) and red mud activator (Na2O·Al2O3·SiO2) under alkaline conditions.
[0049] The Na2O in red mud provides a strong alkaline environment (pH>13) to dissolve the Ca in steel slag. 2+ 、[SiO4] 4- and [AlO4] 5- monomer, forming [Si(OH)4] - and [Al(OH)4] - Precursor. The polycondensation reaction produces C-(N)-ASH gel with low Ca / Si ratio (0.8-1.2), whose three-dimensional network structure is due to Al 35 Replacement of Si 4+ Forming Q 2 (1Al) bond, improves chemical corrosion resistance (Cl- permeability reduced by 40-60%). This application pre-treats red mud, calcining red mud at 600℃ to break the hematite coating, and increases the effective release rate of Na2O from 35% to 75%.
[0050] The present application doped the nano-silicon cores and added 5 wt% of gas-phase SiO2 nanoparticles (particle size 20 nm) as nucleation sites, thereby increasing the degree of polymerization of the gel and achieving a 28d compressive strength of 65 MPa (45 MPa for the benchmark group).
[0051] The expansion compensation phase is CSA reacting with CaSO4·2H2O to form ettringite (AFt), with an expansion amount ΔV = 2.1-3.4%;
[0052] MgO carbonizes to form magnesite (MgCO3), with an expansion volume ΔV = 4.8-5.7%;
[0053] The interface reinforcement phase is nano-alumina filling micro cracks (particle size <100nm), and calcium sulfate whiskers form a three-dimensional skeleton (aspect ratio >20:1).
[0054] Compared with the prior art, the porous laminated grid ecological revetment material suitable for improving dredged soil green materials and the preparation method thereof described in the present invention have the following advantages:
[0055] This application uses dredged soil as the base, and by adding a composite modifier consisting of 11 components including steel slag powder, red mud activator, calcium sulfoaluminate expander, and activated magnesium oxide, combined with a three-layer permeable laminated grid structure design, it significantly improves the mechanical properties and ecological compatibility of the dredged soil. The improved material has a compressive strength of 5-25MPa and a water permeability coefficient of ≥1.5×10 - 3cm / s, drying shrinkage ≤0.05%, and pH 7.5-8.5. Its porous, laminated grid structure, through a stepped, staggered stacking and interlayer interlocking design, achieves a wave energy dissipation efficiency of ≥65% and a vegetation coverage rate of over 85%. It can be widely used in ecological revetment projects along coasts, canals, and lakes. DETAILED DESCRIPTION
[0056] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0057] The present invention will be described in detail below with reference to examples.
[0058] Example 1
[0059] A green improver for dredged soil, comprising 30 parts of steel slag powder (D50≤50μm), a red mud activator (pre-treated with potassium dihydrogen phosphate and calcined at 600℃, with a specific surface area of ≥150m 2 / g) 25 parts, diatomaceous earth (modified nanoporous structure with pore size of 10-50 nm) 11 parts, biochar (product of anaerobic pyrolysis of agricultural and forestry waste at 500°C) 10 parts, calcium lignin sulfonate (purity ≥90%) 6 parts, anionic polyacrylamide (molecular weight 8-12 million) 4 parts, nano-alumina (γ phase, particle size ≤100 nm) 3 parts, calcium sulfate whiskers (aspect ratio 20:1-30:1) 2 parts, calcium sulfoaluminate expander (CSA, Ca4Al6SO 16 ) 4.5 parts, active magnesium oxide (MgO, specific surface area ≥ 200m 2 / g, citric acid coated) 2.5 parts, sodium silicate powder (modulus 2.8-3.0) 2 parts.
[0060] The molar ratio of calcium sulfoaluminate expansion agent to calcium sulfate whiskers is 1:1.4, and the carbonization reaction rate of activated magnesium oxide matches the dredged soil solidification process within ±15%.
[0061] A method for preparing a porous laminated grid ecological bank protection material comprises the following steps:
[0062] a) Add the above-mentioned improver at 20% of the dry mass of the dredged soil and mix well;
[0063] b) stirring the mixture at 70 rpm for 6 minutes to form a homogeneous slurry;
[0064] c) injecting the slurry into a mold and molding it into a hollow laminated grid unit at a pressure of 30-45 MPa using a hydraulic molding machine;
[0065] d) Naturally curing for 28 days in an environment with a relative humidity of ≥70% and a temperature of 25°C to form a bank protection material with a compressive strength of 18.2 MPa.
[0066] The porous laminated grid structure consists of several sequentially arranged single-layer mesh panels, which are staggered and stacked in a stepped manner. Ribs are provided between the single-layer mesh panels. The single-layer mesh panels are provided with inverted conical protrusions above and grooves corresponding to the inverted conical protrusions below. The inverted conical protrusions mechanically interlock the single-layer mesh panels. The single-layer mesh panels are arranged in an array of orthogonal diamond holes with a diameter of 80-120mm. The ribs are 50-80mm wide. The staggered distance of the porous laminated grid structure is 1 / 3-1 / 2 of the aperture diameter. The inverted conical protrusions are 5-8mm high and have an inclination angle of 45°-60°. The sides of the ribs are provided with V-shaped root guide grooves with a width of 3-5mm. Vertical water seepage channels with a diameter of 10-15mm are provided vertically between the layers of the single-layer mesh panels.
[0067] The open-hole laminated grid design of Example 1 increases the wave force attenuation rate by 40% (compared to the solid structure); the wave scour durability mass loss rate of Example 1 is 2.3%.
[0068] The interlayer interlocking structure improves overall shear strength, with the shear strength of Example 1 being ≥3.2 MPa. Citric acid-coated MgO delays the carbonization peak until the 7th-10th day of curing. The compression molding pressure is linked to the curing humidity to avoid premature structural damage.
[0069] Table 1 Performance comparison of 28-day-old
[0070] index The present invention Cement-stabilized soil Improvement rate Compressive strength (MPa) 18.2-25.3 8-15 +103% <![CDATA[Coefficient of permeability (×10 -3 cm / s)]]> 1.5-2.2 0.3-0.8 +367% Vegetation coverage (%) 85-92 30-45 +193%
[0071] Example 2
[0072] A green improver for dredged soil, comprising 30 parts of steel slag powder (D50≤50μm), a red mud activator (pre-treated with potassium dihydrogen phosphate and calcined at 600℃, with a specific surface area of ≥150m 2 / g) 25 parts, diatomaceous earth (modified nanoporous structure with a pore size of 10-50 nm) 10 parts, biochar (product of anaerobic pyrolysis of agricultural and forestry waste at 500°C) 10 parts, calcium lignin sulfonate (purity ≥90%) 6 parts, anionic polyacrylamide (molecular weight 8-12 million) 4 parts, nano-alumina (γ phase, particle size ≤100 nm) 3 parts, calcium sulfate whiskers (aspect ratio 20:1-30:1) 2 parts, calcium sulfoaluminate expander (CSA, Ca4Al6SO 16 ) 5 parts, active magnesium oxide (MgO, specific surface area ≥ 200m 2 / g, citric acid coated) 3 parts, sodium silicate powder (modulus 2.8-3.0) 2 parts.
[0073] The molar ratio of calcium sulfoaluminate expansion agent to calcium sulfate whiskers is 1:1.4, and the carbonization reaction rate of activated magnesium oxide matches the dredged soil solidification process within ±15%.
[0074] A method for preparing a porous laminated grid ecological bank protection material comprises the following steps:
[0075] a) Add the above-mentioned improver at 20% of the dry mass of the dredged soil and mix well;
[0076] b) stirring the mixture at 70 rpm for 6 minutes to form a homogeneous slurry;
[0077] c) injecting the slurry into a mold and molding it into a hollow laminated grid unit at a pressure of 30-45 MPa using a hydraulic molding machine;
[0078] d) Naturally curing for 28 days in an environment with a relative humidity of ≥70% and a temperature of 25°C to form a bank protection material with a compressive strength of 18.2 MPa.
[0079] The porous laminated grid structure consists of several sequentially arranged single-layer mesh panels, which are staggered and stacked in a stepped manner. Ribs are provided between the single-layer mesh panels. The single-layer mesh panels are provided with inverted conical protrusions above and grooves corresponding to the inverted conical protrusions below. The inverted conical protrusions mechanically interlock the single-layer mesh panels. The single-layer mesh panels are arranged in an array of orthogonal diamond holes with a diameter of 80-120mm. The ribs are 50-80mm wide. The staggered distance of the porous laminated grid structure is 1 / 3-1 / 2 of the aperture diameter. The inverted conical protrusions are 5-8mm high and have an inclination angle of 45°-60°. The sides of the ribs are provided with V-shaped root guide grooves with a width of 3-5mm. Vertical water seepage channels with a diameter of 10-15mm are provided vertically between the layers of the single-layer mesh panels.
[0080] The drying shrinkage of the porous laminated grid structure is 0.03%, and the chloride ion diffusion coefficient is 1.8×10 -12 m 2 / s.
[0081] Comparative Example 1
[0082] The difference from Example 1 is that the dredged soil green improver is as follows: 55 parts of steel slag powder (D50 ≤ 50 μm), 11 parts of diatomaceous earth (modified nanoporous structure with a pore size of 10-50 nm), 10 parts of biochar (product of anaerobic pyrolysis of agricultural and forestry waste at 500°C), 6 parts of calcium lignin sulfonate (purity ≥ 90%), 4 parts of anionic polyacrylamide (molecular weight 8-12 million), 3 parts of nano-alumina (γ phase, particle size ≤ 100 nm), 2 parts of calcium sulfate whiskers (aspect ratio 20:1-30:1), and 1 part of calcium sulfoaluminate expander (CSA, Ca4Al6SO 16) 4.5 parts, active magnesium oxide (MgO, specific surface area ≥ 200m 2 / g, citric acid coated) 2.5 parts, sodium silicate powder (modulus 2.8-3.0) 2 parts.
[0083] The wave force attenuation coefficient of Comparative Example 1 is 0.6, the wave scour durability mass loss rate of Comparative Example 1 is 3.2%, and the shear strength of Comparative Example 1 is 3.0 MPa.
[0084] Comparative Example 2
[0085] A green improver for dredged soil, comprising 41 parts of steel slag powder (D50≤50μm), a red mud activator (pretreated with potassium dihydrogen phosphate and calcined at 600℃, with a specific surface area of ≥150m 2 / g) 26 parts, biochar (product of 500℃ anoxic pyrolysis of agricultural and forestry waste) 10 parts, calcium lignin sulfonate (purity ≥90%) 6 parts, anionic polyacrylamide (molecular weight 8-12 million) 4 parts, nano-alumina (γ phase, particle size ≤100nm) 3 parts, calcium sulfate whiskers (aspect ratio 20:1-30:1) 2 parts, calcium sulfoaluminate expander (CSA, Ca4Al6SO 16 ) 4.5 parts, active magnesium oxide (MgO, specific surface area ≥ 200m 2 / g, citric acid coated) 2.5 parts, sodium silicate powder (modulus 2.8-3.0) 2 parts.
[0086] The wave force attenuation coefficient of Comparative Example 2 is 0.6, the wave scour durability mass loss rate of Comparative Example 2 is 3.5%, and the shear strength of Comparative Example 2 is 3.0 MPa.
[0087] Comparative Example 3
[0088] A green improver for dredged soil, comprising 40 parts of steel slag powder (D50≤50μm), a red mud activator (pretreated with potassium dihydrogen phosphate and calcined at 600℃, with a specific surface area of ≥150m 2 / g) 25 parts, diatomaceous earth (modified nanoporous structure with a pore size of 10-50 nm) 11 parts, calcium lignin sulfonate (purity ≥90%) 6 parts, anionic polyacrylamide (molecular weight 8-12 million) 4 parts, nano alumina (γ phase, particle size ≤100 nm) 3 parts, calcium sulfate whiskers (aspect ratio 20:1-30:1) 2 parts, calcium sulfoaluminate expansion agent (CSA, Ca4Al6SO 16 ) 4.5 parts, active magnesium oxide (MgO, specific surface area ≥ 200m 2 / g, citric acid coated) 2.5 parts, sodium silicate powder (modulus 2.8-3.0) 2 parts.
[0089] The wave force attenuation coefficient of Comparative Example 3 is 0.65, the wave scour durability mass loss rate of Comparative Example 3 is 3.5, and the shear strength of Comparative Example 3 is 2.8 MPa.
[0090] Comparative Example 4: A green improver for dredged soil, 36 parts of steel slag powder (D50≤50μm), red mud activator (pretreated with potassium dihydrogen phosphate and calcined at 600℃, with a specific surface area of ≥150m 2 / g) 25 parts, diatomaceous earth (modified nanoporous structure with a pore size of 10-50 nm) 11 parts, biochar (product of anaerobic pyrolysis of agricultural and forestry waste at 500°C) 10 parts, anionic polyacrylamide (molecular weight 8-12 million) 4 parts, nano-alumina (γ phase, particle size ≤ 100 nm) 3 parts, calcium sulfate whiskers (aspect ratio 20:1-30:1) 2 parts, calcium sulfoaluminate expansion agent (CSA, Ca4Al6SO 16 ) 4.5 parts, active magnesium oxide (MgO, specific surface area ≥ 200m 2 / g, citric acid coated) 2.5 parts, sodium silicate powder (modulus 2.8-3.0) 2 parts.
[0091] The wave force attenuation coefficient of Comparative Example 4 is 0.6, the wave scour durability mass loss rate of Comparative Example 4 is 4.5%, and the shear strength of Comparative Example 4 is 2.8 MPa.
[0092] Comparative Example 5
[0093] A green improver for dredged soil, comprising 34 parts of steel slag powder (D50 ≤ 50 μm), a red mud activator (pre-treated with potassium dihydrogen phosphate and calcined at 600 ° C, with a specific surface area ≥ 150 m 2 / g) 25 parts, diatomaceous earth (modified nanoporous structure with a pore size of 10-50 nm) 11 parts, biochar (product of anaerobic pyrolysis of agricultural and forestry waste at 500°C) 10 parts, calcium lignin sulfonate (purity ≥90%) 6 parts, nano-alumina (γ phase, particle size ≤100 nm) 3 parts, calcium sulfate whiskers (aspect ratio 20:1-30:1) 2 parts, calcium sulfoaluminate expander (CSA, Ca4Al6SO 16 ) 4.5 parts, active magnesium oxide (MgO, specific surface area ≥ 200m 2 / g, citric acid coated) 2.5 parts, sodium silicate powder (modulus 2.8-3.0) 2 parts.
[0094] The wave force attenuation coefficient of Comparative Example 5 is 0.55, the wave scour durability mass loss rate of Comparative Example 5 is 4.5%, and the shear strength of Comparative Example 5 is 1.8 MPa.
[0095] Comparative Example 6
[0096] A green improver for dredged soil, comprising 33 parts of steel slag powder (D50 ≤ 50 μm), a red mud activator (pre-treated with potassium dihydrogen phosphate and calcined at 600 ° C, with a specific surface area ≥ 150 m 2 / g) 25 parts, diatomaceous earth (modified nanoporous structure with a pore size of 10-50 nm) 11 parts, biochar (product of anaerobic pyrolysis of agricultural and forestry waste at 500°C) 10 parts, calcium lignin sulfonate (purity ≥90%) 6 parts, anionic polyacrylamide (molecular weight 8-12 million) 4 parts, calcium sulfate whiskers (aspect ratio 20:1-30:1) 2 parts, calcium sulfoaluminate expander (CSA, Ca4Al6SO 16 ) 4.5 parts, active magnesium oxide (MgO, specific surface area ≥ 200m 2 / g, citric acid coated) 2.5 parts, sodium silicate powder (modulus 2.8-3.0) 2 parts.
[0097] The wave force attenuation coefficient of Comparative Example 6 is 0.6, the wave scour durability mass loss rate of Comparative Example 6 is 2.8%, and the shear strength of Comparative Example 6 is 2.3 MPa.
[0098] Comparative Example 7
[0099] A green improver for dredged soil, comprising 30 parts of steel slag powder (D50≤50μm), a red mud activator (pre-treated with potassium dihydrogen phosphate and calcined at 600℃, with a specific surface area of ≥150m 2 / g) 25 parts, diatomaceous earth (modified nanoporous structure with a pore size of 10-50 nm) 11 parts, biochar (product of anaerobic pyrolysis of agricultural and forestry waste at 500°C) 10 parts, calcium lignin sulfonate (purity ≥90%) 6 parts, anionic polyacrylamide (molecular weight 8-12 million) 4 parts, nano alumina (γ phase, particle size ≤100 nm) 3 parts, calcium sulfoaluminate expander (CSA, Ca4Al6SO 16 ) 6.5 parts, active magnesium oxide (MgO, specific surface area ≥ 200m 2 / g, citric acid coated) 2.5 parts, sodium silicate powder (modulus 2.8-3.0) 2 parts.
[0100] The wave force attenuation coefficient of Comparative Example 7 is 0.6, the wave scour durability mass loss rate of Comparative Example 7 is 3.6%, and the shear strength of Comparative Example 7 is 2.2 MPa.
[0101] Comparative Example 8
[0102] A green improver for dredged soil, comprising 30 parts of steel slag powder (D50≤50μm), a red mud activator (pre-treated with potassium dihydrogen phosphate and calcined at 600℃, with a specific surface area of ≥150m 2 / g) 25 parts, diatomaceous earth (modified nanoporous structure with pore size of 10-50nm) 11 parts, biochar (product of anaerobic pyrolysis of agricultural and forestry waste at 500℃) 10 parts, calcium lignin sulfonate (purity ≥90%) 6 parts, anionic polyacrylamide (molecular weight 8-12 million) 4 parts, nano-alumina (γ phase, particle size ≤100nm) 3 parts, calcium sulfate whisker (aspect ratio 20:1-30:1) 6.5 parts, activated magnesium oxide (MgO, specific surface area ≥200m 2 / g, citric acid coated) 2.5 parts, sodium silicate powder (modulus 2.8-3.0) 2 parts.
[0103] The wave force attenuation coefficient of Comparative Example 8 is 0.6, the wave scour durability mass loss rate of Comparative Example 8 is 5.5%, and the shear strength of Comparative Example 8 is 2.6 MPa.
[0104] Comparative Example 9
[0105] A green improver for dredged soil, comprising 32.5 parts of steel slag powder (D50≤50μm), a red mud activator (pretreated with potassium dihydrogen phosphate and calcined at 600℃, with a specific surface area of ≥150m 2 / g) 25 parts, diatomaceous earth (modified nanoporous structure with pore size of 10-50 nm) 11 parts, biochar (product of anaerobic pyrolysis of agricultural and forestry waste at 500°C) 10 parts, calcium lignin sulfonate (purity ≥90%) 6 parts, anionic polyacrylamide (molecular weight 8-12 million) 4 parts, nano-alumina (γ phase, particle size ≤100 nm) 3 parts, calcium sulfate whiskers (aspect ratio 20:1-30:1) 2 parts, calcium sulfoaluminate expander (CSA, Ca4Al6SO 16 ) 4.5 parts, sodium silicate powder (modulus 2.8-3.0) 2 parts.
[0106] The wave force attenuation coefficient of Comparative Example 9 is 0.6, the wave scour durability mass loss rate of Comparative Example 9 is 2.4%, and the shear strength of Comparative Example 9 is 3.0 MPa.
[0107] Comparative Example 10
[0108] A green improver for dredged soil, comprising 30 parts of steel slag powder (D50≤50μm), a red mud activator (pre-treated with potassium dihydrogen phosphate and calcined at 600℃, with a specific surface area of ≥150m 2 / g) 25 parts, diatomaceous earth (modified nanoporous structure with pore size of 10-50 nm) 11 parts, biochar (product of anaerobic pyrolysis of agricultural and forestry waste at 500°C) 10 parts, calcium lignin sulfonate (purity ≥90%) 6 parts, anionic polyacrylamide (molecular weight 8-12 million) 4 parts, nano-alumina (γ phase, particle size ≤100 nm) 3 parts, calcium sulfate whiskers (aspect ratio 20:1-30:1) 2 parts, calcium sulfoaluminate expander (CSA, Ca4Al6SO 16 ) 4.5 parts, active magnesium oxide (MgO, specific surface area ≥ 200m 2 / g, without citric acid coating treatment) 2.5 parts, sodium silicate powder (modulus 2.8-3.0) 2 parts.
[0109] The wave force attenuation coefficient of Comparative Example 10 is 0.65, the wave scour durability mass loss rate of Comparative Example 10 is 3.5%, and the shear strength of Comparative Example 10 is 2.5 MPa.
[0110] Comparative Example 11
[0111] A green improver for dredged soil, comprising 32 parts of steel slag powder (D50 ≤ 50 μm), a red mud activator (pre-treated with potassium dihydrogen phosphate and calcined at 600 ° C, with a specific surface area ≥ 150 m 2 / g) 25 parts, diatomaceous earth (modified nanoporous structure with pore size of 10-50 nm) 11 parts, biochar (product of anaerobic pyrolysis of agricultural and forestry waste at 500°C) 10 parts, calcium lignin sulfonate (purity ≥90%) 6 parts, anionic polyacrylamide (molecular weight 8-12 million) 4 parts, nano-alumina (γ phase, particle size ≤100 nm) 3 parts, calcium sulfate whiskers (aspect ratio 20:1-30:1) 2 parts, calcium sulfoaluminate expander (CSA, Ca4Al6SO 16 ) 4.5 parts, active magnesium oxide (MgO, specific surface area ≥ 200m 2 / g, citric acid coating treatment) 2.5 parts.
[0112] The wave force attenuation coefficient of Comparative Example 11 is 0.6, the wave scour durability mass loss rate of Comparative Example 11 is 3.5%, and the shear strength of Comparative Example 11 is 3.0 MPa.
[0113] According to Examples 1 and 2 of the present application, the present application pioneered the "industrial solid waste ternary composite gelling system" (steel slag + red mud + CSA), which increased the gelling activity by 2.6 times (compared with patent CN110950552A, the prior art); achieved breakthroughs in ecological performance: heavy metal solidification rate ≥ 99.5% (Cd, Pb ion concentration < 0.01 mg / L), and the amount of biological attachment on the revetment surface reached 1.2 kg / m 2 .
[0114] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A green improver for dredged soil, characterized by: The components include the following by mass percentage: 20-30 parts of steel slag powder; 15-25 parts of red mud activator; 10-15 parts of diatomaceous earth; 8-12 parts of biochar; 5-8 parts of calcium lignin sulfonate; 3-5 parts of anionic polyacrylamide; 2-4 parts of nano-alumina; 1-3 parts calcium sulfate whiskers; 3-6 parts of calcium sulfoaluminate expansion agent; 2-4 parts of activated magnesium oxide; 1-3 parts of sodium silicate powder.
2. The green improver for dredged soil according to claim 1, characterized in that: D50 of steel slag powder ≤ 50μm; The red mud activator is pretreated with potassium dihydrogen phosphate and calcined at 600℃, with a specific surface area of ≥150m 2 / g; Diatomaceous earth is a modified nanoporous structure with a pore size of 10-50nm; Biochar is the product of pyrolysis of agricultural and forestry waste at 500°C in the absence of oxygen; The purity of calcium lignin sulfonate is ≥90%; The molecular weight of anionic polyacrylamide is 8-12 million; Nano-alumina is γ phase and the particle size is ≤100nm; The aspect ratio of calcium sulfate whiskers is 20:1-30:1; Calcium sulfoaluminate expansion agents are CSA and Ca4Al6SO 16 ; The specific surface area of active magnesium oxide is ≥200m 2 / g, and the active magnesium oxide is coated with citric acid; The modulus of sodium silicate powder is 2.8-3.
0.
3. The green improver for dredged soil according to claim 1, characterized in that: The molar ratio of the calcium sulfoaluminate expansion agent to the calcium sulfate whisker is 1:1.2-1.5; And / or, the carbonization reaction rate of the activated magnesium oxide matches the dredged soil solidification process within a degree of ±15%.
4. A method for preparing a porous laminated grid ecological revetment material suitable for improving dredged soil green materials, characterized by: The steps include: S1: dry-mixing the dredged soil green improver according to any one of claims 1 to 3 with dredged soil, and stirring to form a homogeneous slurry; S2: injecting the homogenized slurry into the mold and pressing it into a hollow laminated grid unit through a hydraulic molding machine; S3: Carry out natural maintenance on the permeable laminated grid units to form a permeable laminated grid ecological bank protection material suitable for the improvement of dredged soil green materials.
5. The method for preparing a porous laminated grid ecological revetment material suitable for improving dredged soil green materials according to claim 4, characterized in that: In step S1, the dredged soil green improver is added at 8-15% of the dry mass of the dredged soil; The stirring to form a homogeneous slurry includes using a double-shaft forced mixer to stir at a speed of 60-80 r / min for 5-8 minutes to form a homogeneous slurry.
6. The method for preparing a porous laminated grid ecological revetment material suitable for improving dredged soil green materials according to claim 4, characterized in that: In step S2, a hydraulic molding machine is molded into a hollow laminated grid unit at a pressure of 15-25 MPa.
7. The method for preparing a porous laminated grid ecological revetment material suitable for improving dredged soil green materials according to claim 4, characterized in that: In step S2, the open laminated grid structure includes a plurality of single-layer mesh surfaces arranged in sequence, wherein the single-layer mesh surfaces are stacked in a stepped manner, and ribs are provided between the single-layer mesh surfaces; An inverted cone-shaped protrusion is provided above the single-layer mesh surface, and a groove corresponding to the inverted cone-shaped protrusion is provided below the single-layer mesh surface. Mechanical interlocking is achieved between several single-layer mesh surfaces through the inverted cone-shaped protrusions.
8. The method for preparing a porous laminated grid ecological revetment material suitable for improving dredged soil green materials according to claim 7, characterized in that: The single-layer mesh surface is distributed in an array of orthogonal diamond holes, and the aperture of the orthogonal diamond holes of the single-layer mesh surface is 80-120mm; The rib width is 50-80mm; the offset distance of the open laminated grid structure is 1 / 3-1 / 2 of the aperture. The height of the inverted cone-shaped protrusion is 5-8 mm, and the inclination angle is 45°-60°; The side of the rib plate is provided with a V-shaped root guide groove with a width of 3-5mm, and vertical seepage channels with a diameter of 10-15mm are vertically provided between the layers of the single-layer mesh surface.
9. The permeable laminated grid ecological revetment material improved with green materials of dredged soil prepared by the method for preparing the permeable laminated grid ecological revetment material suitable for improving green materials of dredged soil according to claims 4-8 is characterized by: The compressive strength of the porous laminated grid ecological bank protection material improved with dredged soil green material is 5-25MPa.
10. The improved permeable laminated grid ecological revetment material made of dredged soil green material according to claim 9, characterized in that: The wave force attenuation coefficient η of the permeable laminated grid ecological revetment material improved with dredged soil green material satisfies: η = 1-HtHi ≥ 0.65, and the test conditions are wave period T = 5s and wave height H = 2m; where Ht is the transmitted wave height, in meters; Hi is the incident wave height, in meters.
Citation Information
Cited By
Ecological bank protection material and manufacturing method thereof
CN121248210A
Ecological revetment material and method for manufacturing the same
CN121248210B